TAFSIR AL-FATIHAH: (Studi Literatur Kitab Tafsir Bimakna Petuk) - Nisa', Mir’atun (QOF, 2018)
Hidayatut Thulab is one of the pesantren in Kediri, East Java, which publishes many books, especially the book of morality and interpretation. Achmad Asymuni and his son Achmad Yasin Asmuni as caretakers of the Hidayatut Thulab pesantren are among the ulamas and kiai in Kediri, who are very productive in their work. This article aims to analyze one of the books by Achmad Yasin Asymuni entitled Tafsir al-Fatihah, the book of interpretation of his work is usually called tafsir bimakna petuk. The analysis was carried out using the Islah Gusmian text analysis framework with regard to the technical aspects of writing and hermeneutic aspects. From this analysis it can be seen that in the technical aspect of writing this interpretation adopts coherent systematic, detailed presentation form with persuasive exposition language style and non-scientific reference sources. As for the hermeneutic aspect, this interpretation has a Sufic theological nuance. In addition, the book of interpretation of al-Fatihah uses makna gandul with Java-pegon script by affixing the symbol of the position of the word in Arabic grammar in almost all words.